Establishment of regularities of isothermal flow and mixture formation in microjet burners with three-row jet fuel supply - Fialko, Nataliia; Meranova, Nataliia; Sherenkovskii, Julii; Aleshko, Sergey; Abdulin, Michael; Babak, Vitalii; Korzhyk, Volodymyr; Zhelykh, Vasyl; Dinzhos, Roman; Khaskin, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2022)
The object of this research is the aerodynamics and mixture formation of fuel and oxidizer in stabilizer-type burners with a three-row system of fuel jets, focused on operation at coefficients of excess air 1.1...1.5. The study was conducted on the basis of CFD modeling using the RANS (Reynolds Averaged Navier-Stokes) approach. The analysis of the basic regularities of the course of these processes in the proposed microjet burners was carried out. In this case, special attention was paid to the consideration of the characteristics of flow and mixture formation in the aft region of the flame stabilizer, where vortex structures are formed that are responsible for stabilizing the torch. The regularities of influence on the flow and mixture formation in the proposed burner devices of such factors as the row number NR of the jet fuel supply, the relative pitch, S/d, of the location of gas supply holes and the coefficient of excess air, α, have been investigated. The presence of noticeable differences in the structure of flow and mixture formation in burners during fuel supply to different rows of gas supply holes has been established. It is shown that aerodynamics and the pattern of mixing fuel and oxidizer undergo significant changes when varying the value of S/d. For the considered burner devices, rational design parameters of the fuel supply system have been determined, at which favorable conditions for mixture formation in the field of flame stabilization are ensured. In particular, it is shown that the rational S/d values are 5.4; 5.6; and 5.8, respectively, for the first, second, and third sections of the fuel supply. The results can be widely used in energy practice for objects operated under conditions of variable values of the coefficient of excess air